Self-reported Impact of the Early 2020 COVID-19 Crisis on the Healthcare Pathway During and After Lockdown in Patients With Chronic Immune-Mediated Inflammatory Diseases: A Practical Survey. (December 2022) - Nasseh, Jessica; Podevin, Céline; Ternynck, Camille; Zephir, Hélène; Letarouilly, Jean-Guillaume; Flipo, René-Marc; Nachury, Maria; Chenivesse, Cécile; Hachulla, Eric; Launay, David; Staumont-Salle, Delphine; Dezoteux, Frédéric
Introduction: Global lockdown in the context of the coronavirus disease 2019 (COVID-19) pandemic is an unprecedented experience. We report here the results of an anonymous questionnaire-based survey on the healthcare and control of chronic IMIDs (chronic immune-mediated inflammatory diseases) within the IMMINENT network during the French lockdown (March 17, 2020-May 11, 2020) and the 2-month period following the end of the lockdown (July 11, 2020).Methods: Two anonymous questionnaires were sent by email to 4500 patients who were followed in a university hospital for an IMID in the departments of gastroenterology, rheumatology, dermatology, pneumology, neurology, and internal medicine.Results: A total of 921/4500 (20.46%) responded to the first survey (impact of the lockdown), and 553/4500 (12.28%) to the second (impact at 2-months post-lockdown). Concerning the impact of the lockdown, 420/915 (45.9%) reported affected follow-up. Similarly, after the lockdown, 248/544 (45.6%) declared a negative impact on their follow-up. The repartition by departments of patients' perception of an altered follow-up during ( P  = .72) and at the end of the lockdown ( P  = .77) was not statistically different. Our study highlighted the effects of the COVID-19 pandemic and the restriction measures implemented on the self-reported impact felt by patients on the follow-up of their chronic IMIDs without significant differences among all departments.Conclusion: Our study is original by showing that patients, whatever the type of IMID, shared this same negative perception. This transdisciplinary study demonstrated the importance of a collaborative network among all departments.